The synagogue as a religious and community space - Leone, Alexandre (2019)
The synagogue has become during the last two thousand years the main place where Jewish public liturgies are held. This article deals with the external and internal architectural aspects of synagogues and their use as religious and community space through the centuries. In addition to the architecture and organization of the synagogue space, the collective liturgical use of this type of place of worship is also addressed. The versatility and permanence of this institution are also addressed.